Направления активизации деятельности туристических предприятий промышленных регионов - Данильчук, В.Ф. (Інститут економіки промисловості НАН України, 2006)
Обґрунтовано напрями активізації діяльності туристичних підприємств промислових регіонів, реалізація яких створює передумови для розвитку всього комплексу сфери туризму країни.
---------- Обоснованы направления активизации деятельности туристических предприятий промышленных регионов, реализация которых создает предпосылки для развития всего комплекса сферы туризма страны.
---------- The questions concerning organization of financial provision for innovative processes in the coal production are considered. The principle of organization of financing provides variety of sources and assumes fast and effective introduction of innovations. The opportunities of financing of innovations from different sources are considered taking into consideration the specific features of the coal mines.
----------